Treatment outcomes of multidrug-resistant tuberculosis in Hangzhou, China, 2011 to 2015. Issue 30 (24th July 2020) - Li, Qingchun; Shi, Cynthia X.; Lu, Min; Wu, Limin; Wu, Yifei; Wang, Meng; Wang, Le; Zhao, Gang; Xie, Li; Qian, Han-Zhu
Abstract : Abstract: Treatment of multidrug-resistant tuberculosis (MDR-TB) is challenging. More research is needed to understand treatment outcomes and associated factors. A retrospective cohort study was conducted to assess trends and predictors of treatment success among 398 MDR-TB and extensively drug resistant TB patients who started treatment in 2011 to 2015 in Hangzhou, China. Sociodemographic and clinical characteristic data were obtained from the national reporting database. Chi-square test for trend was used to evaluate changes in treatment success rates over the study years, and Cox regression analysis was used to identify predictors for poor treatment outcomes. The treatment success rate was 76% (301/398) for all participants, 77% (298/387) for MDR-TB cases and 27% (3/11) for extensively drug-resistant tuberculosis -TB cases. Treatment success increased significantly from 66% among patients who started treatment in 2011 to 85% in 2015 ( P  < .01). Of the 97 (24.4%) patients with unsuccessful treatment outcomes, 10 (2.5%) died, 64 (16.1%) failed treatment, and 23 (5.8%) were lost to follow-up. Patients who started treatment in 2013 to 2015 were less likely to have unsuccessful outcomes than those who started in 2011–2012 (adjusted odds ratio [AOR] 0.4, 95% confidence interval [CI] 0.3–0.6), patients ≥25 years were more likely to have unsuccessful outcomes than younger patients (AOR 1.6, 95% CI 1.3–2.1), and cases with kanamycin resistance was associated with three times the odds of having unsuccessful outcomes than kanamycin-susceptible cases (AOR 3.0, 95% CI 1.5–5.8). With proper case management of MDR-TB, patients can achieve a high treatment success rate. Hangzhou's program offers clinical evidence that can be used to inform MDR-TB programs elsewhere in China and abroad.